2012
DOI: 10.1128/jcm.06293-11
|View full text |Cite
|
Sign up to set email alerts
|

The Geographic Origin of Helicobacter pylori Influences the Association of the homB Gene with Gastric Cancer

Abstract: We found that South Korean Helicobacter pylori isolates predominantly carry homB at locus B and that there is no association between the homB allele and the cagA allele or the development of gastric cancer within this population. Uniquely, several East Asian strains carried multiple copies of the hom genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 20 publications
4
48
1
Order By: Relevance
“…The s1/m1 or s2/m2 displays the genotype of i1 and i2, respectively, while the s1/m2 displays genotype of i1 or i2. The relationship between i genotype and disease is region dependent[21,22]. Both the S1 and S2 are not pathogenic.…”
Section: Polymorphisms Of H Pylori Virulence Genesmentioning
confidence: 99%
“…The s1/m1 or s2/m2 displays the genotype of i1 and i2, respectively, while the s1/m2 displays genotype of i1 or i2. The relationship between i genotype and disease is region dependent[21,22]. Both the S1 and S2 are not pathogenic.…”
Section: Polymorphisms Of H Pylori Virulence Genesmentioning
confidence: 99%
“…The large group of OMPs contains adhesins (BabA and SabA), adherence-associated lipoproteins (AlpA/B) and infl ammatory OMPs (OipA or HomB) that mediate H. pylori binding to the host cell membrane. Some of these OMPs are associated with more severe pathologies, such as HomB in ulcers [ 19 ] and cancer [ 10 ]. The babA genotype correlates with the highest incidence of ulceration and gastric cancer [ 24 ].…”
Section: H Pylori Virulence Factorsmentioning
confidence: 99%
“…9,10 Another group of proteins that is highly variable between strains is the OMPs. [18][19][20][21][22][23] Unfortunately, we were unable to identify a definitive genotype that was indicative of disease progression; however, the observed association between homA/homB/homC and cagA, vacA and the bab subfamily led us to investigate the Hom OMP family in greater detail. Additionally, recent studies have proposed the necessity of OMPs for efficient delivery of CagA to the host cell.…”
mentioning
confidence: 96%
“…Each of these polymorphic regions is subsequently divided into two types (type 1 and type 2), and the type 1 variants are associated with higher cell toxicity and more severe disease outcome following H. pylori infection. [18][19][20][21][22][23] The culmination of those studies revealed two themes: (1) there is a high level of variation observed in the AH population as compared to the near homogenous profile of the KH population and (2) the OMP profile of a strain can be used as an indicator of its geographic origin. OMPs provide a key interface between Gram-negative pathogens and their environment and may serve as a genetic determinant of disease outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation